2021
DOI: 10.1038/s41598-021-95505-6
|View full text |Cite
|
Sign up to set email alerts
|

Failure of diffusion-weighted imaging in intraoperative 3 Tesla MRI to identify hyperacute strokes during glioma surgery

Abstract: Intraoperatively acquired diffusion-weighted imaging (DWI) sequences in cranial tumor surgery are used for early detection of ischemic brain injuries, which could result in impaired neurological outcome and their presence might thus influence the neurosurgeon’s decision on further resection. The phenomenon of false-negative DWI findings in intraoperative magnetic resonance imaging (ioMRI) has only been reported in single cases and therefore yet needs to be further analyzed. This retrospective single-center stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Especially in patients with a glioblastoma, the existence of perifocal DWI hyperintensities is a very poor prognostic factor [ 14 ], i.e., the complete resection of such diffusion-restricted tumor tissue is particularly important. A Swiss study showed the limitations of DWI and that intraoperative infarctions in particular can be overlooked or underestimated [ 15 ]. There are different study results on the existence and prognostic value of postoperative infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in patients with a glioblastoma, the existence of perifocal DWI hyperintensities is a very poor prognostic factor [ 14 ], i.e., the complete resection of such diffusion-restricted tumor tissue is particularly important. A Swiss study showed the limitations of DWI and that intraoperative infarctions in particular can be overlooked or underestimated [ 15 ]. There are different study results on the existence and prognostic value of postoperative infarcts.…”
Section: Discussionmentioning
confidence: 99%
“… 36 However, it should be noted that there is a report that the hyperacute ischemic change could not be detected even by 3 T ioMR imaging. 37 Therefore, one cannot exclusively rely on ioMR to determine possible complications.…”
Section: Why Do Neurosurgeons Need Iomr Images?mentioning
confidence: 99%